2010
DOI: 10.1136/jnnp.2010.212225
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, genetic and pathological heterogeneity of frontotemporal dementia: a review

Abstract: Frontotemporal dementia (FTD) is the second most common young-onset dementia and is clinically characterised by progressive behavioural change, executive dysfunction and language difficulties. Three clinical syndromes, behavioural variant FTD, semantic dementia and progressive non-fluent aphasia, form part of a clinicopathological spectrum named frontotemporal lobar degeneration (FTLD). The classical neuropsychological phenotype of FTD has been enriched by tests exploring Theory of Mind, social cognition and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
404
3
27

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(444 citation statements)
references
References 211 publications
10
404
3
27
Order By: Relevance
“…Correspondingly, executive dysfunctions are closely related to WM abnormalities in T2DM. At the same time, many investigations have found that FTD affects executive function through regional disruption of the frontal and temporal lobes (44), where the more severely disrupted WM tracts were found in T2DM. Therefore, we predict that T2DM might be associated with FTD.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, executive dysfunctions are closely related to WM abnormalities in T2DM. At the same time, many investigations have found that FTD affects executive function through regional disruption of the frontal and temporal lobes (44), where the more severely disrupted WM tracts were found in T2DM. Therefore, we predict that T2DM might be associated with FTD.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in GRN account for 5-10% of all the FTLD cases. 10,11 Deletions of one copy of GRN have been reported, 12,13 but the majority of mutations result in null alleles, leading to an approximately 50% reduction of the precursor protein GRN, which can be measured in serum, plasma and CSF. [14][15][16] Mutations in GRN have been reported in different clinical phenotypes including Alzheimer disease (AD) and corticobasal syndrome (CBS).…”
Section: Introductionmentioning
confidence: 99%
“…Patients referred for FDG-PET had a younger mean age than patients referred for DaTscan, consistent with the younger age at onset of FTD. 1 The gender spread was biased towards male patients, particularly in the group referred for DaTscan. This may reflect the small sample size, but also suggests a preponderance of suspected DLB in male patients, as has been described previously.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fronto-temporal dementia (FTD) is different from Alzheimer's disease (AD) in terms of earlier age of onset, higher genetic burden, prominent behavioural symptoms and poor response to acetylcholine-esterase inhibitors (ACIs). 1 NICE clinical guidelines recommend that structural neuroimaging with CT or MRI should be performed at least once in ever y patient with suspected dementia and that functional neuroimaging with HMPAO-SPECT or FDG-PET should be considered to help differentiate between AD, vascular dementia (VaD) and FTD if the diagnosis is in doubt. 2 European guidelines state that FDG-PET is particularly useful in differentiating AD from FTD with more than 95% specificity in young onset dementia.…”
mentioning
confidence: 99%